CYBERSECURITY DEVELOPMENT IN THELITERATURE FROM 2020 TO 2024 - González, María del Rosario Molina (IPHO-Journal of Advance Research in Science And Engineering, 2024)
Local Development is a process that aims to promote sustainability by discussing and reaching a consensus on resource allocation, opportunities, capabilities, and municipal responsibilities. The objective of this work is to establish the relationship between these aspects through a desk study. The study consists of three phases. In the first phase, we selected databases representative of LatinAmericansources with ISSN and DOI registration is-sued during the period from 2020-2024. In the second phase, we analyzed the information using content analysis to identify the topics of discussion. The third phase involves contrasting the selected information with a specific case of endogenous development. Finally, we compare the themes based on the state ofknowledge.